Synthesis and characterization of polyvinyl alcohol/polyaniline/functionalized multiwalled carbon nanotube nanocomposite film by gamma- radiation method - Haji Othman, Norfazlinayati (2018)
Polyaniline/multiwalled carbon nanotubes (PANI/MWCNT) nanocomposite is one type of materials that has properties that are unique and improved as compared to the nature of the individual original materials. However, the fabrication process to apply the nanocomposite to the industry is quite complicated especially in producing a versatile free standing film. The hindrances that are encountered included inhomogeneous composite film, high cost, unclean procedure, difficult to dispose chemical residues and limitation to scale up for mass commercialization. These are among the main factors that scientists and researchers need to resolve before the material can be used commercially. After evaluating different synthesizing techniques, it was decided that gamma-radiation method has the potential to be a promising ecofriendly technique where no oxidizing agent or any surfactant agent was needed and the purity of products is maintained. In this research project, a free standing film of polyaniline (PANI) and polyaniline/functionalized-multiwalled carbon nanotubes (PANI/f-MWCNTs) with different f-MWCNT composition were synthesized in the PVA matrix by γ -radiation method. All films were exposed to gamma-rays from 10 to 50 kGy. The structural, morphological, chemical composition, chemical bonding, electronic transition, optical energy band gap, degree of disorder of band tail and thermal properties of PVA/PANI composite film and PVA/PANI/f- MWCNT nanocomposite films before and after irradiated by gamma-radiation were characterized by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray (EDAX), Fourier Transform Infrared Spectroscopy (FTIR), UV-Visible (UV-Vis) Spectrophotometer and Thermogravimetric Analysis (TGA). Morphology of the f-MWCNT obtained from FESEM after irradiation show that the nanotube diameter changes by about 70% to 90% as compared to the original size before irradiation. XRD confirmed that all the characteristic crystalline peaks after irradiation at 50 kGy represent the structure of PANI in emeraldine salt form which was 2θ= 21.9, 22.0, 22.8, 23.9, 27.5 and 35.6°. However, after the addition of f-MWCNT in the composite system, the intensity of the dominant peak of PANI (2θ = 21°) decreased with the increasing of f-MWCNT content at the highest irradiation dose. It is believed that there is a strong reaction exists between PANI and f-MWCNT. FTIR spectrum showed that the functional group from f-MWCNT (-COOH) has attached to the secondary of amides from PANI monomer and quinoid unit in the nanocomposite film is richer (IQ/IB=1.17) as compared to unirradiated film (IQ/IB=1.12). It is believed that more conjugated PANI has fully coated over the nanotube sidewall during polymerization process initiated by gammaradiation. This was further confirmed by UV-Vis analysis that showed the П - П * transition of phenylene rings increasingly red-shifted and polaron- П* transition has a blue-shifted whereby it may assign to the presence of more extended chains of PANI network wrapped on f-MWCNT sidewalls. The calculated value for the optical energy band gap for the nanocomposite film decreases after irradiation which was from 3.33 for 0 kGy to 2.62 eV for 50 kGy. This suggests that the resultant composite is more conductive as compared to the unirradiated film. It was also observed that the degree of disorder in the nanocomposite film also decreased which was from 0.42 to 0.34 eV at 0 kGy and 50 kGy, respectively. This indicates that the structure formed was more ordered after irradiation and thus showed that electric and electronic properties have improved. This can also be seen through the results by TGA technique in which the thermal properties of the nanocomposite film was highly stable due after the irradiation process. This can be observed at maximum temperature (700 °C) in which the total weight loss for the film before the radiation is 96.69 % as compared to the film after irradiation which is 82.83 %. Results from all characterizations indicated that synthesis of PVA, PANI and f- MWCNT through the gamma-radiation was successful in producing a homogeneous free standing film of PVA/PANI composite film and PVA/PANI/f-MWCNT nanocomposite films. The structural, morphological, optical energy band gap, degree of disorder of the band tail and thermal properties of these composite and nanocomposite films was significantly improves as compared to other methods.